Odpowiedzi

2009-11-24T14:33:55+01:00
1 - x²-4 = 2(x² - 6x - 9) - 3x²
1- x²-4 = 2x² - 12x - 18 -3x²
12x = 4 -1 + 18
12x = 21 / : 12
x = 1,75
2009-11-24T14:45:32+01:00
1-(x +2)(x-2) = 2(x-3)² - 3x²
1 - x² - 2x + 2x - 4 = 2 (x² - 9) - 3x²
1 - x² - 4 = 2x² - 18 - 3x²
x² - 2x² + 3x² = 18 + 4 - 1
2x² = 21 / : 2
x² = 10,5 / pierwiastek
x = 3,24
Najlepsza Odpowiedź!
2009-11-24T15:13:05+01:00
1-(x +2)(x-2) = 2(x-3)² - 3x²
1-x²-4= 2(x²-6x+9) - 3x²
1 - x² - 4 = 2x² - 12x + 18 - 3x²
-x² -2x² -12x -3x² = -1 +4 +18
-12x = 21 / : (-12)
x= -1,75